Purification and characterization of a keratinolytic serine protease from Purpureocillium lilacinum LPS # 876 - Cavello, Ivana Alejandra (2013)
A keratinolytic serine protease secreted by Purpureocillium lilacinum (formerly Paecilomyces lilacinus) upon culture in a basal medium containing 1% (w/v) hair waste as carbon and nitrogen source was purified and characterized. After purification the keratinase was resolved by SDS-PAGE as a homogeneus protein band of molecular mass 37.0 kDa. The extracellular keratinase of P. lilacinum was characterized by its appreciable stability over a broad pH range (from 4.0 to 9.0), and up to 65 °C, along with its strong inhibition by phenylmethylsulphonyl fluoride among the protease inhibitors tested (98.2% of inhibition), thus suggesting its nature as a serine protease. The enzyme was active and stable in the presence of organic solvents such as dimethylsulfoxide, methanol, and isopropanol; certain surfactants such as Triton X-100, sodium dodecylsulfate, and Tween 85; and bleaching agents such as hydrogen peroxide. These biochemical characteristics suggest the potential use of this enzyme in numerous industrial applications.